ANALYSIS OF SERVICE ANALYSIS OF SERVICE QUALITY TO BRI BANK CUSTOMER'S SATISFACTION UNIT PERDAGANGAN: ANALYSIS OF SERVICE QUALITY TO BRI BANK CUSTOMER'S SATISFACTION UNIT PERDAGANGAN - Diana Florenta Butarbutar; Hamela Sari Sitompul (Institute of Computer Science (IOCS), 2021)
PT. Bank Rakyat Indonesia Perdagangan unit is one of the banks operating among the many banks in the Perdagangan area. The higher level of competition between banks (local competition) to win customers in the Perdagangan region occurs with other banks that are increasingly appearing to compete for markets / customers. This research was conducted to determine how much influence the quality of service on customer satisfaction BRI Perdagangan unit bank. This research uses descriptive research type with quantitative approach. The research method used by the author uses a questionnaire with a sample of 70 people where the respondent is a customer of Bank Rakyat Indonesia Perdagangan unit. Based on the t-test (Partial Significant Test), service quality characteristics have a positive and significant effect on customer satisfaction of the BRI Bank Perdagangan unit. The majority of respondents were satisfied with the services provided by the BRI Bank Perdagangan Unit through the answers they gave to the questionnaire that had been distributed.